Regional concentration of knowledge intensive business services in Europe - Xavier Vence; Manuel Gonzalez (European Regional Science Association (ERSA), 2010)
This paper aims to contribute toa better understanding of the Knowledge Intensive Services spatial distribution across the European Union(EU) regions(NUTSII), linking recent research approaches on innovation and structural change with approaches to regional economics. As a means of conducting this research, we classify economic activities according to six sectors based on their knowledge/technology intensity. Our results show that the higher the knowledge/technology content of the economic activity, the higher the concentration level of the activity.
Keywords: R1; L84; 330; KIBS; concentration; agglomeration economies; spatial difussion